Modeling of longitudinal balancing the flying machine in system MatLab - Жданов, С. В.; Єгоров, С. Н. (Proceedings of National Aviation University (archive), 2021)
It is considered problem of modeling of longitudal balancing the flying machine. Algorithm of decision of supplieded problem is developped. It is brought block diagram of modeling, listings of the main block and results of modeling for plane IL-76T.